THE MORAL PHENOMENON OF SERVICE - Moiseenko, M.V. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Filosofii͡a, 2017)
This article examines the phenomenon of moral Service, highlights the main value com-ponents of the concept of Service. The phenomenon is investigated mainly through the prism of social Service in the forms of charity and benevolence drawn from the history and from modern Russia. The enor-mous role of the state and state ideology that guides society with high moral standards is emphasized in the article. Social Service in the forms of charity and philanthropy has deep roots in Russian history, starting from the first Russian princes and the clergy. The mercy is always seen in the history of Russia as the highest value. In modern Russia the strong focus is also set on the acts of mercy. Multiple awards and state prizes have been given to citizens and organizations supporting orphanages, nursing homes, hospices and medical institutions located on the territory of the Russian Federation. The Service is regarded as a form of patriotism. The article highlights the importance of the personality of the teacher in moral and patriotic upbringing of the younger generation. The appeal to the themes of patriotism and Service is illustrated by the example of the Colloquiums of the Department of Ethics within the framework of the educational work in RUDN. In conclusion the author defines the basic moral values of people who devoted their lives to the high ideals of Service. According to the author, this is: patriotism, humanistic aspirations, open-mindedness, high moral ideals, highly developed sense of duty, honor and dignity, tender conscience, altruistic motives, hard work, professionalism, priority of spiritual values over material, self-sacrifice. Service is a feat in a long-term perspective.